Right To Recall Political Representatives: Legal Audit of Article 85 Passage (1) Letter C Of Regulation Number 22 of 2003 And Article 12 Letter B Of Regulation Number 31 Of The Year 2002 - Ngateman Ngateman; Endang Kusuma Astuti (CV. Publikasi Indonesia, 2023)
The overall game plans for pardoning people from the DPR are contained in Article 22 B of the 1945 Constitution of the Republic of Indonesia read